Clinical prognostic characteristics of ocular mucoepidermoid carcinoma: a retrospective study - Li, Jing; Yang, Runzi; Liu, Rui; Wang, Nan; Zhang, Hong; Ma, Jianmin (Frontiers in Oncology, 2026)
AimThis study aimed to characterize the clinical presentation, pathological features, and prognostic indicators of ocular mucoepidermoid carcinoma (MEC) based on an institutional cohort and a systematic literature review.MethodsA retrospective analysis was conducted including two distinct datasets: six patients with histopathologically confirmed ocular MEC treated at our institution and twenty-one cases identified through literature review. Institutional cases were evaluated for clinical course, treatment, and recurrence, whereas literature-derived cases were summarized descriptively due to reporting heterogeneity and incomplete follow-up.ResultsPatients in the institutional cohort (n = 6) had a median age of 64 years, with no sex predominance. The lacrimal gland was the most frequent primary site, followed by the eyelid and lacrimal sac. The predominant manifestation was a painless orbital mass, while diplopia and visual loss were less frequent. Intermediate-grade lesions were most common, and orbital tissue invasion was histologically confirmed in two patients. Both patients with invasion experienced tumor recurrence, whereas no recurrence was observed among patients without invasion during follow-u No disease-related deaths occurred within this cohort. The literature-derived group demonstrated substantial variability in grading, invasion patterns, and follow-up duration, reflecting selective reporting toward advanced or recurrent cases.ConclusionsOcular MEC demonstrates a high tendency toward local recurrence but generally low disease-specific mortality. Orbital tissue invasion appears to be associated with an elevated risk of recurrence in the institutional cohort, underscoring the need for prolonged surveillance. Given the marked heterogeneity of published cases, survival inference should be limited to consistently followed institutional data.